Complete genome sequencing and comparative plasmid analysis of KPC-2-producing Klebsiella pneumoniae isolated from hospital sewage water in Japan. (March 2021) - Eda, Ryotaro; Maehana, Shotaro; Hirabayashi, Aki; Nakamura, Masaki; Furukawa, Takashi; Ikeda, Shinsuke; Sakai, Kouji; Kojima, Fumiaki; Sei, Kazunari; Suzuki, Masato; Kitasato, Hidero
Abstract: Objectives: The Klebsiella pneumoniae carbapenemase ( bla KPC ) gene is one of the most widespread carbapenemase genes in the world. However, there are few reports on KPC-producing bacteria in Japan. The aim of this study was therefore to investigate KPC-producing K. pneumoniae in Japan. Methods: A KPC-2-producing K. pneumoniae strain (KAM260) was isolated from hospital sewage water in Japan in 2018. The complete genome was determined by whole-genome sequencing. Subsequent comparative sequence analysis of the bla KPC-2 -carrying plasmid was performed. Results: Klebsiella pneumoniae KAM260, belonging to sequence type 3026 (ST3026), harboured the bla KPC-2 gene in 114.6-kbp plasmid pKAM260_2 with IncFIB(pQIL) and IncFII(K) replicons. pKAM260_2 was highly identical to pKpQIL-like plasmids, which carry bla KPC genes and have spread worldwide. pKAM260_2 had functional conjugation-associated genes and was transferable to Escherichia coli . Conclusion: pKAM260_2, the self-transmissible plasmid carrying the bla KPC-2 gene, was detected from hospital sewage water in Japan and was characterised as a pKpQIL-like plasmid. This plasmid needs to be monitored in Japan in the future owing to its high diffusivity.